Pole piece coating, composite pole piece and sodium ion battery
By optimizing parameters such as the solid content, surface density, and compacted density of the electrode coating, the problem of poor performance of sodium iron sulfate sodium-ion batteries at ultra-high rates was solved, good cell performance and stability were achieved at ≥50C, and the discharge capacity retention rate and rate performance were improved.
Patent Information
- Application Number
- CN202510453846.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-11
- Publication Date
- 2025-10-10
AI Technical Summary
Existing sodium iron sulfate sodium-ion batteries have difficulty maintaining good cell performance in ultra-high rate scenarios, especially in the ultra-high rate discharge field of ≥50C, where they are rarely used.
By regulating parameters such as the solid content, surface density, compaction density and resistivity of the electrode coating, the composition of the positive and negative electrode composite slurries is optimized to form electrode coatings with a specific range, including a positive electrode coating formed by coating the positive electrode composite slurry on the surface of the positive electrode current collector, and a negative electrode coating formed by coating the negative electrode composite slurry on the surface of the negative electrode current collector, thereby improving the transmission performance of electrons and sodium ions, reducing resistance, and enhancing electronic conductivity and ion movement channels.
It significantly improves the discharge capacity retention and rate performance of sodium-ion batteries at ultra-high rates of ≥50C, avoids uneven coating and sodium precipitation, extends battery life, and improves the stability and high-rate performance of the battery cells.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a pole piece coating, a composite pole piece and a sodium ion battery. Background Art
[0002] Sodium iron sulfate sodium-ion battery is a battery that uses sodium ions as charge carriers. The battery is charged and discharged by inserting and separating sodium ions between the positive and negative electrodes. Compared with lithium-ion batteries, sodium-ion batteries can operate in a wider temperature range, are less flammable, and have a longer cycle life, making them a beneficial supplement to lithium-ion batteries.
[0003] With the development of the industry, the demand for high-rate sodium iron sulfate batteries is becoming increasingly prominent. High-rate batteries have the ability to quickly charge and discharge in a short period of time, and are widely used in 3C electronic products, power tools, drones, industrial power supplies, automotive emergency power supplies, model aircraft, and other fields. However, existing sodium iron sulfate sodium-ion batteries have difficulty maintaining good cell performance in ultra-high rate scenarios, resulting in limited application of sodium iron sulfate sodium-ion batteries in the ultra-high rate discharge field of ≥50C. Summary of the Invention
[0004] In response to the problems existing in the above-mentioned prior art, the present application provides a pole piece coating, a composite pole piece, and a sodium ion battery, which can have excellent performance at an ultra-high rate of ≥50C. The technical solution is as follows: In one aspect, the present application provides a pole piece coating, comprising at least one of a positive electrode coating and a negative electrode coating, wherein the positive electrode coating is formed by coating a positive electrode composite slurry on the surface of a positive electrode current collector, and the negative electrode coating is formed by coating a negative electrode composite slurry on the surface of a negative electrode current collector; The solid content of the positive electrode composite slurry is 55% to 70%; and / or The solid content of the negative electrode composite slurry is 40% to 55%.
[0005] Furthermore, the pole piece coating satisfies at least one of the following characteristics: The surface density of the positive electrode coating is 3 mg / cm 2 ~10mg / cm 2 ; The surface density of the negative electrode coating is 1 mg / cm 2 ~5mg / cm 2 .
[0006] Furthermore, the pole piece coating satisfies at least one of the following characteristics: The compaction density of the positive electrode coating is 1.5 g / cm 3 ~2.5g / cm 3 ; The compaction density of the negative electrode coating is 0.7 g / cm 3 ~1.3g / cm 3 .
[0007] Furthermore, a preset ratio between the capacity of the negative electrode coating and the capacity of the positive electrode coating is 1.0 to 2.0.
[0008] Furthermore, the pole piece coating satisfies at least one of the following characteristics: The resistivity of the positive electrode coating is 1Ω﹒ cm to 5Ω﹒ cm; The resistivity of the negative electrode coating is 0.05Ω﹒cm to 1.0Ω﹒cm.
[0009] Furthermore, the solid components in the positive electrode composite slurry include a positive electrode active material, a positive electrode binder, and a positive electrode conductor, and the positive electrode composite slurry satisfies at least one of the following characteristics: The positive electrode active material includes sodium iron sulfate positive electrode material; The positive electrode binder includes one or more of polyvinylidene fluoride, polymethyl methacrylate, polytetrafluoroethylene, polystyrene butadiene copolymer, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylic acid and polyvinylidene fluoride-hexafluoropropylene; The positive electrode conductive agent includes one or more of graphite, superconducting carbon, acetylene black, conductive carbon black, carbon nanotubes, graphene, carbon nanofibers, metal powder, metal fibers and polyphenylene derivatives.
[0010] Furthermore, the solid components in the negative electrode composite slurry include a negative electrode active material, a negative electrode binder, and a negative electrode conductive agent, and the negative electrode composite slurry meets at least one of the following characteristics: The negative electrode active material includes a hard carbon material; The negative electrode binder includes one or more of polyvinylidene fluoride, polymethyl methacrylate, polytetrafluoroethylene, styrene-butadiene rubber, polystyrene-butadiene copolymer, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylic acid and polyvinylidene fluoride-hexafluoropropylene; The negative electrode conductive agent includes one or more of graphite, superconducting carbon, acetylene black, conductive carbon black, carbon nanotubes, graphene, carbon nanofibers, metal powder, metal fibers and polyphenylene derivatives.
[0011] On the other hand, the present application also provides a composite electrode, comprising a current collector and a electrode coating as described in any of the above items, wherein the current collector comprises at least one of a positive electrode current collector and a negative electrode current collector, the positive electrode coating covers the surface of the positive electrode current collector, and the negative electrode coating covers the surface of the negative electrode current collector.
[0012] On the other hand, the present application also provides a sodium ion battery comprising the composite electrode as described above.
[0013] Furthermore, the sodium ion battery satisfies at least one of the following characteristics: The discharge capacity retention rate of the sodium ion battery at 50C is greater than or equal to a first target retention rate, and the first target retention rate is 75% to 80%; The discharge capacity retention rate of the sodium ion battery at 60C is greater than or equal to a second target retention rate, and the second target retention rate is 70% to 75%; The discharge capacity retention rate of the sodium ion battery at 80C is greater than or equal to a third target retention rate, and the third target retention rate is 65% to 70%; The discharge capacity retention rate of the sodium ion battery at 100C is greater than or equal to a fourth target retention rate, and the fourth target retention rate is 60% to 64%.
[0014] The implementation of this application has the following beneficial effects: 1. This application uses a positive electrode composite slurry with a solid content of 55% to 70% to form a positive electrode coating, and / or a negative electrode composite slurry with a solid content of 40% to 55% to form a negative electrode coating, which can effectively reduce the resistance of the electrode coating, while improving the dispersion uniformity of the active material in the slurry, improving the coating effect, and avoiding the increase in the resistance of the electrode coating, thereby jointly improving the rate performance of the sodium ion battery with the electrode coating, especially improving its high-rate performance at ≥50C.
[0015] 2. This application effectively improves the transmission performance of electrons and sodium ions in the electrode coating by regulating the surface density of the electrode coating, reduces the charge transfer resistance, and improves the rate performance of the sodium ion battery with the electrode coating; at the same time, it avoids foil leakage due to uneven coating, thereby avoiding sodium precipitation during the battery cell cycle.
[0016] 3. This application reduces the distance between particles, improves contact tightness, and enhances electronic conductivity by regulating the compaction density of the electrode coating. At the same time, it maintains a certain ion movement channel, increases the liquid absorption of the electrolyte, and is conducive to the rapid movement of a large number of ions. The sodium ion battery with this electrode coating can achieve high current discharge and avoid discharge polarization, greatly improving the performance of the battery cell.
[0017] 4. This application regulates the solid content of the composite slurry, the coating surface density and the compaction density of the electrode coating. The three work together to greatly reduce the surface resistance of the electrode coating, so that the electrode coating has good high-rate performance. After being applied to sodium-ion batteries, it can still have good battery cell performance at a high rate of ≥50C. DETAILED DESCRIPTION
[0018] The following is a clear and complete description of the technical solutions in the embodiments of this application. Obviously, the embodiments described are only part of the embodiments of this application, not all of them, and therefore should not be understood as limiting this application. Based on the embodiments of this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.
[0019] It should be noted that in the description of this application, for the following defined terms, these definitions should be applied unless a different definition is given in the claims or elsewhere in this specification. All numerical values, whether or not explicitly indicated, are defined herein as being modified by the term "about". The term "about" generally refers to a numerical range that a person of ordinary skill in the art would consider to be equivalent to the stated value to produce substantially the same properties, functions, results, etc. A numerical range indicated by a low value and a high value is defined to include all numerical values included in the numerical range and all subranges included in the numerical range.
[0020] It should be noted that the terms "first", "second" etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequential order. It should be understood that the objects used in this way can be interchanged in appropriate circumstances, so that the embodiments of the present application can be implemented in the order except the following description. In addition, the terms "comprise" and "have" and their any deformation are intended to cover non-exclusive inclusions, for example, the process, method, system, product comprising a series of steps or units need not be limited to those steps or units clearly listed, but may include other steps or units not clearly listed or inherent to these processes, methods, or products.
[0021] In order to solve the problem in the prior art that sodium ion batteries are difficult to work stably at an ultra-high rate of 50C or more, an embodiment of the present application provides a pole piece coating, including at least one of a positive electrode coating and a negative electrode coating, the positive electrode coating is formed by coating the positive electrode composite slurry on the surface of the positive electrode current collector, and the negative electrode coating is formed by coating the negative electrode composite slurry on the surface of the negative electrode current collector; wherein the solid content refers to the total mass proportion of the solid components including the active material, the conductive agent and the binder in the electrode composite slurry in the electrode composite slurry, which can affect the rheological properties and coating process of the electrode composite slurry; for example, the positive electrode solid content refers to the total mass proportion of the solid components including the positive electrode active material, the positive electrode conductive agent and the positive electrode binder in the positive electrode composite slurry in the positive electrode composite slurry, and the negative electrode solid content refers to the total mass proportion of the solid components including the negative electrode active material, the negative electrode conductive agent and the negative electrode binder in the negative electrode composite slurry in the negative electrode composite slurry; by regulating the solid content of the positive electrode composite slurry within the desired range, and / or adjusting Controlling the solid content of the negative electrode composite slurry within the desired range can effectively reduce the resistance of the formed electrode coating, avoid the uneven coating caused by the low viscosity of the electrode composite slurry and easy sedimentation and stratification, and avoid the situation where the viscosity of the electrode composite slurry is too high and the coating resistance is increased, reduce streaks or cracks, improve the dispersion effect of the active material in the slurry and the coating effect, which is beneficial to improving the rate performance of the battery cell, especially the performance of the battery cell at an ultra-high rate of ≥50C; in some exemplary embodiments, the electrode coating includes a positive electrode coating, thereby improving the performance of the positive electrode coating, and further improving the rate performance of the sodium ion battery having the positive electrode coating; in other exemplary embodiments, the electrode coating includes a negative electrode coating, improving the performance of the negative electrode coating, so as to improve the rate performance of the sodium ion battery having the negative electrode coating; in some preferred embodiments, the electrode coating includes a positive electrode coating and a negative electrode coating, which can further improve the high rate performance of the sodium ion battery having the positive electrode coating and the negative electrode coating.
[0022] Specifically, the solid components in the positive electrode composite slurry include positive electrode active materials, positive electrode binders and positive electrode conductors; wherein the positive electrode active materials include sodium ferric sulfate positive electrode materials, that is, the positive electrode composite slurry is suitable for improving the performance of sodium ferric sulfate sodium ion batteries at ultra-high rates greater than or equal to 50C.
[0023] Among them, the positive electrode binder includes one or more of polyvinylidene fluoride, polymethyl methacrylate, polytetrafluoroethylene, polystyrene butadiene copolymer, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylic acid and polyvinylidene fluoride-hexafluoropropylene. The positive electrode binder is used to improve the adhesion reliability between the positive electrode coating and the positive electrode collector, improve the structural stability of the positive electrode coating and the positive electrode collector, so that sodium ions can be transmitted stably and effectively, which is beneficial to prolong the life of the positive electrode coating and the sodium ion battery.
[0024] The positive electrode conductive agent includes one or more of graphite, superconducting carbon, acetylene black, conductive carbon black, carbon nanotubes, graphene, carbon nanofibers, metal powder, metal fibers and polyphenylene derivatives, which can effectively reduce the contact resistance between the positive electrode coating and the positive electrode current collector, improve the ionic conductivity, and help improve the charge and discharge performance of the positive electrode coating.
[0025] Specifically, the solid content of the positive electrode composite slurry is 55% to 70%; it can be understood that the solid content of the positive electrode composite slurry can be any point value between 55% and 70%; for example, the solid content of the positive electrode composite slurry can be 55%, 58%, 60%, 62%, 65%, 67%, 70%, etc.; within this solid content range, the positive electrode coating formed after coating can have a relatively low membrane resistance, which is beneficial to improving the rate performance of the battery cell, that is, the sodium ion battery; at the same time, it avoids the low viscosity of the positive electrode composite slurry caused by too low solid content. Sedimentation and stratification can also avoid streaks or cracks caused by excessive solid content, excessive slurry viscosity, and excessive coating resistance, and can improve the dispersion effect of the positive electrode active material in the positive electrode composite slurry, improve the distribution uniformity of the conductive agent and the positive electrode active material therein, thereby improving the coating effect, avoiding the increase of the membrane resistance, and also helping to improve the rate performance of the battery cell, so that the sodium ion battery with the positive electrode coating still has good performance at an ultra-high rate greater than or equal to 50C; in some preferred embodiments, the solid content of the positive electrode composite slurry is 58% to 68%.
[0026] Specifically, the surface density of the positive electrode coating is 3 mg / cm 2 ~10mg / cm 2 It can be understood that the surface density of the positive electrode coating can be 3mg / cm 2 ~10mg / cm 2 For example, the surface density of the positive electrode coating can be 3 mg / cm 2 , 4mg / cm 2 , 5mg / cm 2 , 6mg / cm 2 , 7mg / cm 2 , 7mg / cm 2 , 9mg / cm 2 , 10mg / cm 2etc.; within this surface density range, it is possible to avoid sodium ions passing through the thickness of the positive electrode coating and its diffusion path when the surface density is too high, effectively alleviate the aggravation of concentration polarization, and prevent the electrons in the thick positive electrode coating from needing to pass through a longer conductive network, which causes the ohmic impedance to increase significantly, effectively improving the transmission performance of electrons and sodium ions in the positive electrode coating, reducing the charge transfer resistance, and thus improving the rate performance of the battery cell; at the same time, it also avoids the occurrence of foil leakage, uneven coating, and other phenomena such as sodium precipitation during the battery cell cycle, thereby improving the cycle stability of the sodium ion battery at high rates; it can also reduce the risk of cracking and falling off of the positive electrode due to the volume change of the active material during the charge and discharge process of the electrode coating, thereby slowing down the capacity decay; in addition, it can avoid the effect of too low a surface density on the energy density of the positive electrode coating and the sodium ion battery, thereby reducing the cost; in some preferred embodiments, the surface density of the positive electrode coating is 3.5 mg / cm 2 ~6mg / cm 2 .
[0027] Specifically, the compacted density of the positive electrode coating is 1.5 g / cm 3 ~2.5g / cm 3 It can be understood that the compaction density of the positive electrode coating can be 1.5g / cm 3 ~2.5g / cm 3 For example, the compaction density of the positive electrode coating can be 1.5 g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 2.0g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.5g / cm 3 etc.; at this compaction density, the distance between particles is moderate and the contact is close, which improves the contact probability and contact area between particles, is conducive to enhancing electronic conductivity, thereby facilitating large-current discharge and reducing discharge polarization; at the same time, it avoids the reduction or blocking of ion movement channels due to too small spacing. There are relatively more ion channels in the positive electrode coating, and the liquid absorption of the electrolyte is increased, which facilitates the rapid movement of a large number of ions. It is also beneficial for the sodium ion battery with the positive electrode coating to perform large-current discharge, reduce polarization during discharge, and improve the rate performance and stability of the sodium ion battery at an ultra-high rate of greater than or equal to 50C; in some preferred embodiments, the compaction density of the positive electrode coating is 1.8g / cm 3 ~2.2g / cm 3 .
[0028] Specifically, the resistivity of the positive electrode coating is 1Ω﹒ cm to 5Ω﹒ cm; it can be understood that the resistivity of the positive electrode coating can be any point value in the range of 1Ω﹒ cm to 5Ω﹒ cm; illustratively, the resistivity of the positive electrode coating can be 1Ω﹒ cm, 1.5Ω﹒ cm, 2Ω﹒ cm, 2.5Ω﹒ cm, 3Ω﹒ cm, 4Ω﹒ cm, 5Ω﹒ cm, etc.; in this way, compared with the traditional unregulated positive electrode coating, the resistivity can be reduced by more than 20%. The resistivity of the positive electrode coating is relatively small, which is beneficial to improving the rate performance of the positive electrode coating and the sodium ion battery, especially the rate performance at 50C or above.
[0029] Specifically, the solid components in the negative electrode composite slurry include negative electrode active materials, negative electrode binders and negative electrode conductors. The negative electrode active materials include hard carbon materials, which can improve the performance of the hard carbon negative electrode at an ultra-high rate of 50C or higher.
[0030] Among them, the negative electrode binder includes one or more of polyvinylidene fluoride, polymethyl methacrylate, polytetrafluoroethylene, styrene-butadiene rubber, polystyrene butadiene copolymer, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylic acid and polyvinylidene fluoride-hexafluoropropylene. The negative electrode binder is used to improve the adhesion reliability between the negative electrode coating and the negative electrode current collector and prevent it from falling off, so that ions and electrons can be effectively and stably transmitted during the operation of the sodium ion battery, which is also beneficial to improving the life of the negative electrode coating and the sodium ion battery.
[0031] The negative electrode conductive agent includes one or more of graphite, superconducting carbon, acetylene black, conductive carbon black, carbon nanotubes, graphene, carbon nanofibers, metal powder, metal fibers and polyphenylene derivatives, which improves the electronic conductivity and is beneficial to improving the charge and discharge performance of the negative electrode.
[0032] Specifically, the solid content of the negative electrode composite slurry is 40% to 55%; it can be understood that the solid content of the negative electrode composite slurry can be any point value between 40% and 55%; for example, the solid content of the negative electrode composite slurry can be 40%, 45%, 47%, 50%, 52%, 53%, 55%, etc.; within this solid content range, the negative electrode coating formed after coating can have a relatively low film resistance, which is beneficial to improving the rate performance of the battery cell; at the same time, it avoids the low viscosity of the negative electrode composite slurry and the easy sedimentation caused by too low solid content. layer, and also avoids stripes or cracks caused by too high solid content, too high slurry viscosity, and too high coating resistance, and can improve the dispersion effect of the negative electrode active material in the negative electrode composite slurry, improve the distribution uniformity of the conductive agent and the negative electrode active material therein, thereby improving the coating effect, avoiding the increase of the membrane resistance, and also helping to improve the rate performance of the battery cell, so that the sodium ion battery with the negative electrode coating still has good performance at an ultra-high rate of greater than or equal to 50C; in some preferred embodiments, the solid content of the negative electrode composite slurry is 46% to 50%.
[0033] Specifically, the surface density of the negative electrode coating is 1 mg / cm 2 ~5mg / cm 2 It can be understood that the surface density of the negative electrode coating can be 1 mg / cm 2 ~5mg / cm 2 For example, the surface density of the negative electrode coating can be 1 mg / cm 2 , 2mg / cm 2 , 2.5mg / cm 2 , 3mg / cm 2 , 4mg / cm 2 , 4.5mg / cm 2 , 5mg / cm 2 etc.; within this surface density range, compared with the situation where ions need to pass through a thicker negative electrode coating at too high a surface density, the diffusion path is extended, resulting in aggravated concentration polarization, and electrons need to pass through a longer conductive network (such as conductive carbon black), which significantly increases the ohmic impedance. The surface density of the negative electrode coating can effectively improve the electron transmission performance in the negative electrode coating, reduce the charge transfer resistance, and thus improve the rate performance of the battery cell; at the same time, it also avoids the phenomenon of sodium precipitation during the battery cell cycle caused by foil leakage and uneven coating, thereby improving the cycle stability of the sodium ion battery at high rates; and it can reduce the risk of cracking and falling off of the negative electrode coating due to the volume change of the active material during the charge and discharge process, effectively slowing down the capacity decay; in addition, it can also avoid the adverse effects of too low a surface density on the final energy density, thereby reducing costs; in some preferred embodiments, the surface density of the negative electrode coating is 2.5 mg / cm 2 ~5mg / cm 2 .
[0034] Specifically, the compaction density of the negative electrode coating is 0.7 g / cm 3 ~1.3g / cm 3 It can be understood that the compaction density of the negative electrode coating can be 0.7g / cm 3 ~1.3g / cm 3 For example, the compaction density of the negative electrode coating can be 0.7 g / cm 3 , 0.8g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3etc. At this compaction density, the inter-particle distance is moderate, the contact is close, the contact probability and contact area between particles are improved, which is conducive to enhancing the electronic conductivity, thereby facilitating large current discharge and reducing discharge polarization. At the same time, the spacing is not too small to reduce or block the ion movement channel. There are relatively more ion channels in the negative electrode coating, the electrolyte absorption capacity increases, and the rapid movement of a large number of ions is also facilitated, thereby facilitating the large current discharge of the sodium ion battery with the negative electrode coating and reducing the polarization during discharge, and improving the rate performance and stability of the sodium ion battery at more than or equal to 50C of the ultra-high rate. In some preferred embodiments, the compaction density of the negative electrode coating is 0.85 g / cm 3 ~ 1.1 g / cm 3 .
[0035] Specifically, the resistivity of the negative electrode coating is 0.05 Ω·cm~1.0 Ω·cm; it can be understood that the resistivity of the negative electrode coating can be any point value in 0.05 Ω·cm~1.0 Ω·cm; for example, the resistivity of the negative electrode coating can be 0.05 Ω·cm, 0.1 Ω·cm, 0.2 Ω·cm, 0.5 Ω·cm, 0.55 Ω·cm, 0.75 Ω·cm, 1.0 Ω·cm, etc. In this way, compared with the traditional unregulated negative electrode coating, the resistivity can be reduced by more than 20%, the resistivity of the negative electrode coating is relatively small, which is conducive to improving the rate performance of the negative electrode coating and the sodium ion battery, especially at more than or equal to 50C.
[0036] Specifically, the preset ratio between the capacity of the negative electrode coating and the capacity of the positive electrode coating is 1.0 to 2.0, wherein the capacity of the negative electrode coating is determined based on the mass of the negative electrode active material, the coating surface density of the negative electrode active material and the reversible gram capacity of the negative electrode active material, for example, the capacity of the negative electrode coating can be the product of the mass of the negative electrode active material, the coating surface density of the negative electrode active material and the reversible gram capacity of the negative electrode active material; the capacity of the positive electrode coating is determined based on the mass of the positive electrode active material, the coating surface density of the positive electrode active material and the reversible gram capacity of the positive electrode active material, for example, the capacity of the positive electrode coating is the product of the mass of the positive electrode active material, the coating surface density of the positive electrode active material and the reversible gram capacity of the positive electrode active material; it can be understood that the negative electrode coating has a relatively large capacity, and the capacity of the positive electrode coating has a relatively large capacity. The preset ratio between the capacity of the cathode coating and the capacity of the cathode coating can be any point value between 1.0 and 2.0; illustratively, the preset ratio between the capacity of the anode coating and the capacity of the cathode coating can be 1.0, 1.1, 1.3, 1.5, 1.6, 1.8, 1.9, 2.0, etc.; during the operation of the sodium ion battery, the active material on the positive electrode side will be transferred to the negative electrode coating. Within this preset ratio range, the sites for storing sodium ions in the negative electrode coating are greater than the number of sodium ions that can be provided in the positive electrode coating, which can enable the sodium ions to move stably and quickly, facilitate large current discharge, and improve the high rate performance of the sodium ion battery; in some preferred embodiments, the preset ratio between the capacity of the negative electrode coating and the capacity of the positive electrode coating is 1.1 to 1.5.
[0037] On the other hand, the present application also provides a composite electrode sheet, including a current collector and a electrode sheet coating as described above, the current collector including at least one of a positive electrode current collector and a negative electrode current collector, so as to improve the performance of the composite electrode sheet at an ultra-high rate greater than or equal to 50C; wherein, on the surface of the positive electrode current collector, a positive electrode composite slurry is coated on the surface of the positive electrode current collector, and a positive electrode composite electrode sheet is formed after drying, and the positive electrode coating covers the surface of the positive electrode current collector, so as to improve the performance of the positive electrode composite electrode sheet at an ultra-high rate; on the surface of the negative electrode current collector, a negative electrode composite slurry is coated on the surface of the negative electrode current collector, and a negative electrode coating covers the surface of the negative electrode current collector, so as to improve the performance of the negative electrode composite electrode sheet at an ultra-high rate.
[0038] On the other hand, the present application also provides a sodium ion battery comprising the composite electrode sheet as described above; in some exemplary embodiments, the sodium ion battery comprises a positive composite electrode sheet; in other exemplary embodiments, the sodium ion battery comprises a negative composite electrode sheet; in some preferred embodiments, the sodium ion battery comprises a positive composite electrode sheet and a negative composite electrode sheet, further improving the rate performance of the sodium ion battery at a rate ≥50C.
[0039] Specifically, the sodium ion battery also includes an electrolyte, the solute of the electrolyte is a sodium electrolyte salt, and in some exemplary embodiments, the sodium electrolyte salt includes sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium trifluoromethanesulfonate (NaOTf), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), sodium bisoxalatoborate (NaBOB), sodium difluorooxalatoborate (NaDFOB) and sodium perchlorate (NaClO4). At least one of the solute in the electrolyte The concentration is 0.8 mol / L to 2.0 mol / L, which is beneficial to improving the ion transfer efficiency and ion transfer stability of the sodium ion battery, so that the electrolyte and the sodium ion battery can maintain good performance stability even at ultra-high rates; the solvent of the electrolyte includes one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethyl methyl carbonate, which can maintain a good ion migration rate even at an ultra-high rate of greater than or equal to 50C, and is also beneficial to improving the rate performance of the sodium ion battery.
[0040] Specifically, the discharge capacity retention rate of the sodium ion battery at 50C is greater than or equal to the first target retention rate, and the first target retention rate is 75% to 80%; it can be understood that the first target retention rate can be any point value between 75% and 80%; exemplarily, the first target retention rate can be 75%, 76%, 77.5%, 78%, 79%, 80%, etc., and the sodium ion battery has a good discharge capacity retention rate at a rate of 50C; exemplarily, in some specific embodiments, the first target retention rate is 75%, that is, the discharge capacity retention rate of the sodium ion battery at 50C is greater than or equal to 75%.
[0041] Specifically, the discharge capacity retention rate of the sodium ion battery at 60C is greater than or equal to the second target retention rate, and the second target retention rate is 70% to 75%; it can be understood that the second target retention rate can be any point value between 70% and 75%; exemplarily, the second target retention rate can be 70%, 71%, 72%, 73%, 74%, 75%, etc., and the sodium ion battery has a good discharge capacity retention rate at a rate of 60C; exemplarily, in some specific embodiments, the second target retention rate is 70%, that is, the discharge capacity retention rate of the sodium ion battery at 60C is greater than or equal to 70%.
[0042] Specifically, the discharge capacity retention rate of the sodium ion battery at 80C is greater than or equal to the third target retention rate, and the third target retention rate is 65% to 70%; it can be understood that the third target retention rate can be any point value between 65% and 70%; exemplarily, the third target retention rate can be 65%, 66%, 67%, 68%, 69%, 70%, etc., and the sodium ion battery has a good discharge capacity retention rate at a rate of 80C; exemplarily, in some specific embodiments, the third target retention rate is 65%, that is, the discharge capacity retention rate of the sodium ion battery at 80C is greater than or equal to 65%.
[0043] Specifically, the discharge capacity retention rate of the sodium ion battery at 100C is greater than or equal to the fourth target retention rate, and the fourth target retention rate is 60% to 64%; it can be understood that the fourth target retention rate can be any point value between 60% and 64%; exemplarily, the fourth target retention rate can be 60%, 61%, 62%, 62.5%, 63%, 64%, etc., and the sodium ion battery has a good discharge capacity retention rate at a rate of 100C; exemplarily, in some specific embodiments, the fourth target retention rate is 60%, that is, the discharge capacity retention rate of the sodium ion battery at 100C is greater than or equal to 60%.
[0044] The following describes the embodiments of the present application in combination with the above technical solutions.
[0045] Example 1 The sodium ion battery of this embodiment is prepared by the following steps: 1. Preparation of positive electrode composite pole piece: 90wt% sodium iron sulfate positive electrode active material, 2.5wt% positive electrode binder PVDF (polyvinylidene fluoride), 6wt% positive electrode conductive agent SP (conductive carbon black), 1.5wt% positive electrode conductive agent MWCNT (multi-walled carbon nanotube), NMP (N-methylpyrrolidone) as solvent, prepare positive electrode composite slurry with a solid content of 60%; after stirring the positive electrode composite slurry evenly, apply it on the surface of the positive electrode current collector (carbon-coated aluminum foil), bake it at 85°C, and then roll and die-cut it to obtain a positive electrode composite pole piece with a compaction density of 2g / m 3 After die-cutting and powder coating, the positive electrode composite plate is baked at 100°C for 12 hours; the coating surface density of the positive electrode composite plate is 5mg / cm 2 , resistivity is 3Ω﹒cm.
[0046] 2. Preparation of negative electrode composite sheet: 92.2wt% of negative electrode active material hard carbon, 3.5wt% of negative electrode conductive agent SP, 2.8wt% of negative electrode binder SBR (styrene-butadiene rubber), and 1.2wt% of negative electrode binder CMC (carboxymethyl cellulose) were homogenized in deionized water to obtain a negative electrode composite slurry with a solid content of 48%. Then, it was coated on the negative electrode current collector copper foil, baked at 85°C, and then rolled and die-cut to make the compaction density of the negative electrode composite sheet 0.95g / m 3 After die-cutting and powder coating, the negative electrode composite sheet was baked at 100°C for 12 hours. The coating surface density of the negative electrode composite sheet was 1.2 mg / cm 2 , with a resistivity of 0.1Ω﹒cm. The preset ratio between the capacity of the negative electrode coating and the capacity of the positive electrode coating is 1.2.
[0047] 3. The positive electrode composite electrode sheet and the negative electrode composite electrode sheet are stacked, wound and fixed, and then plastic-sealed. After drying, they are injected into an electrolyte with a sodium electrolyte salt concentration of 1.2 mol / L, a solvent of EC:PC:DEC=4.5:4.5:1, and an acidity of 11.5 for packaging to obtain a sodium ion battery.
[0048] Example 2 The difference between this embodiment and embodiment 1 is that the coating surface density of the positive electrode coating is 10 mg / cm 2 , the resistivity is 7Ω﹒cm; the rest is the same as Example 1.
[0049] Example 3 The difference between this embodiment and embodiment 1 is that the coating surface density of the negative electrode coating is 1.5 mg / cm 2 , the resistivity is 0.15Ω﹒cm; the rest is the same as in Example 1.
[0050] Example 4 The difference between this embodiment and embodiment 1 is that the solid content of the positive electrode composite slurry is 55%; the rest is the same as embodiment 1.
[0051] Example 5 The difference between this embodiment and embodiment 1 is that the solid content of the negative electrode composite slurry is 43%; the rest is the same as embodiment 1.
[0052] Example 6 The difference between this embodiment and embodiment 1 is that the compaction density of the positive electrode coating is 2.5 g / cm 3 ; The rest is the same as Example 1.
[0053] Example 7 The difference between this embodiment and embodiment 1 is that the compaction density of the negative electrode coating is 1.2 g / cm 3; The rest is the same as Example 1.
[0054] Example 8 The difference between this embodiment and embodiment 1 is that the preset ratio between the capacity of the negative electrode coating and the capacity of the positive electrode coating is 1.1; the rest is the same as embodiment 1.
[0055] Comparative Example 1 The difference between this comparative example and Example 1 is that the coating surface density of the positive electrode coating is 12 mg / cm 2 , the resistivity is 9.3Ω﹒cm; the rest is the same as in Example 1.
[0056] Comparative Example 2 The difference between this comparative example and Example 1 is that the solid content of the positive electrode composite slurry is 50%; the rest is the same as Example 1.
[0057] Comparative Example 3 The difference between this comparative example and Example 1 is that the compaction density of the positive electrode coating is 2.8 g / cm 3 ; The rest is the same as Example 1.
[0058] The sodium ion batteries prepared in the above examples and comparative examples were subjected to performance tests, and the test results are shown in Table 1 below.
[0059] Table 1 Performance test results of sodium ion batteries in Examples and Comparative Examples
[0060] As can be seen from Table 1, in Comparative Examples 1-3, the discharge capacity retention rates of the sodium ion batteries are all small, and under the same rate conditions, they are all much smaller than the discharge capacity retention rates of the sodium ion batteries in Examples 1-8; while in Examples 1-8, the discharge capacity retention rate of the sodium ion batteries at 50C is greater than or equal to 75%, the discharge capacity retention rate at 60C is greater than or equal to 70%, the discharge capacity retention rate at 80C is greater than or equal to 65%, and the discharge capacity retention rate at 100C can also reach 64% or more, which is much higher than the discharge capacity retention rates at each high rate in Comparative Examples 1-3, indicating that the sodium iron sulfate sodium ion battery of the embodiment of the present application has a greatly improved discharge capacity retention rate at ultra-high rate compared to the traditional sodium ion battery, and generally has good rate performance at ultra-high rate ≥50C.
[0061] It should be noted that the various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same and similar parts between the various embodiments can be referenced to each other.
[0062] What is described above are only some embodiments of the present application and are not intended to limit the present application. Those skilled in the art should understand that the present application may be subject to various changes and improvements, and any modifications, equivalent substitutions, and improvements made in accordance with the present application shall fall within the scope of protection required by the present application.
Claims
1. A pole piece coating, characterized in that: The positive electrode coating comprises at least one of a positive electrode coating and a negative electrode coating, wherein the positive electrode coating is formed by coating a positive electrode composite slurry on the surface of a positive electrode current collector, and the negative electrode coating is formed by coating a negative electrode composite slurry on the surface of a negative electrode current collector; The solid content of the positive electrode composite slurry is 55% to 70%; and / or The solid content of the negative electrode composite slurry is 40% to 55%.
2. The pole piece coating according to claim 1, characterized in that: The pole piece coating satisfies at least one of the following characteristics: The surface density of the positive electrode coating is 3 mg / cm 2 ~10mg / cm 2 ; The surface density of the negative electrode coating is 1 mg / cm 2 ~5mg / cm 2 .
3. The pole piece coating according to claim 1, characterized in that: The pole piece coating satisfies at least one of the following characteristics: The compaction density of the positive electrode coating is 1.5 g / cm 3 ~2.5g / cm 3 ; The compaction density of the negative electrode coating is 0.7 g / cm 3 ~1.3g / cm 3 .
4. The pole piece coating according to claim 1, characterized in that: The preset ratio between the capacity of the negative electrode coating and the capacity of the positive electrode coating is 1.0 to 2.
0.
5. The pole piece coating according to any one of claims 1 to 4, characterized in that: The pole piece coating satisfies at least one of the following characteristics: The resistivity of the positive electrode coating is 1Ω﹒ cm to 5Ω﹒ cm; The resistivity of the negative electrode coating is 0.05Ω﹒cm to 1.0Ω﹒cm.
6. The pole piece coating according to any one of claims 1 to 4, characterized in that: The solid components in the positive electrode composite slurry include a positive electrode active material, a positive electrode binder, and a positive electrode conductor, and the positive electrode composite slurry meets at least one of the following characteristics: The positive electrode active material includes sodium iron sulfate positive electrode material; The positive electrode binder includes one or more of polyvinylidene fluoride, polymethyl methacrylate, polytetrafluoroethylene, polystyrene butadiene copolymer, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylic acid and polyvinylidene fluoride-hexafluoropropylene; The positive electrode conductive agent includes one or more of graphite, superconducting carbon, acetylene black, conductive carbon black, carbon nanotubes, graphene, carbon nanofibers, metal powder, metal fibers and polyphenylene derivatives.
7. The pole piece coating according to any one of claims 1 to 4, characterized in that: The solid components in the negative electrode composite slurry include a negative electrode active material, a negative electrode binder, and a negative electrode conductive agent, and the negative electrode composite slurry meets at least one of the following characteristics: The negative electrode active material includes a hard carbon material; The negative electrode binder includes one or more of polyvinylidene fluoride, polymethyl methacrylate, polytetrafluoroethylene, styrene-butadiene rubber, polystyrene-butadiene copolymer, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylic acid and polyvinylidene fluoride-hexafluoropropylene; The negative electrode conductive agent includes one or more of graphite, superconducting carbon, acetylene black, conductive carbon black, carbon nanotubes, graphene, carbon nanofibers, metal powder, metal fibers and polyphenylene derivatives.
8. A composite pole piece, characterized in that: It comprises a current collector and a pole piece coating as described in any one of claims 1 to 7, wherein the current collector comprises at least one of a positive electrode current collector and a negative electrode current collector, the positive electrode coating covers the surface of the positive electrode current collector, and the negative electrode coating covers the surface of the negative electrode current collector.
9. A sodium ion battery, characterized in that: Including the composite pole piece as described in claim 8.
10. The sodium ion battery according to claim 9, characterized in that The sodium ion battery meets at least one of the following characteristics: The discharge capacity retention rate of the sodium ion battery at 50C is greater than or equal to a first target retention rate, and the first target retention rate is 75% to 80%; The discharge capacity retention rate of the sodium ion battery at 60C is greater than or equal to a second target retention rate, and the second target retention rate is 70% to 75%; The discharge capacity retention rate of the sodium ion battery at 80C is greater than or equal to a third target retention rate, and the third target retention rate is 65% to 70%; The discharge capacity retention rate of the sodium ion battery at 100C is greater than or equal to a fourth target retention rate, and the fourth target retention rate is 60% to 64%.
Citation Information
Patent Citations
Low-temperature-resistant sodium ion battery
CN113851632A
Negative active layer and secondary battery comprising same
CN117790789A
Secondary battery, preparation method thereof and electric device
CN118099356A